Draft environmental impact statement for the wilderness recommendation : Glacier Bay National Park and Preserve, Alaska. - United States. National Park Service. Alaska Regional Office. (Anchorage, Alaska : Alaska Regional Office, National Park Service, 1988)
"NPS D-26"--P. [3] of cover. Includes index. "April 1988"--P. [3] of cover. Shipping list no.: 88-305-P. Cover title: Draft environmental impact statement : wilderness recommendation : Glacier Bay National Park and Preserve, Alaska. Bibliography: p. 106-109. Mode of access: Internet.